A new comprehensive workflow for modelling outdoor thermal comfort in Egypt. (1st September 2021) - Kamel, Tarek M.
Highlights: Energy building simulations are little based on their effect on the microclimate, most applications deal with energy consumption or the neglect of the Solar Reflective Index (SRI) rule outside. The paper framework introduces a comprehensive simulation workflow of the built environment with the assistance of Ladybug & Honeybee and Butterfly plugins across grasshopper interface to model a shared relationship between urban microclimate, energy building use and thermal comfort outdoors. The result describes the effect of SRI on the outdoor thermal comfort for the pedestrians in existing canyon when defining the finishing materials for the urban zone rather than the rural zone for both districts at the same time the transpiration phenomenon is exempted along the simulation with no effect of vegetation. "Strong heat stress" is the main output conclusion for both districts as mentioned by UTCI stress category and the difference between the urban and rural zones is about 1 °C due to the materials absorption and emissions. Abstract: Energy building simulations are little based on their effect on the microclimate, most of software applications deal with energy consumption for appliances usage electricity for indoor spaces and neglecting the impact of the Solar Reflective Index (SRI) phenomenon for outdoor open spaces. The paper framework introduces a comprehensive simulation workflow of the built environment with the assistance of Ladybug & Honeybee and Butterfly plugins across grasshopper interface to model a shared relationship between urban microclimate, building energy usage, and thermal comfort outdoors. Two districts have been investigated in Egypt, both have different Azimuth and Latitude angle degrees to measure the impact of solar radiation on pedestrians and their outdoor thermal comfort using Mean Radiant Temperature and Universal Thermal Climate Index (UTCI). This workflow provides considerable versatility compared with other current methods and allows parametric study of multiple environment strategies both indoors and outdoors. The result describes the effect of SRI are too noticeable on the outdoor thermal comfort for the pedestrians in existing canyon, especially after defining the material specs and properties for each building. As considerably, the transpiration phenomenon is exempted along the simulation with no effect of vegetation and their humidity affect. "Strong heat stress" is the main output conclusion for both districts as categorized by UTCI stress level and the difference between the condense urban and rural areas from measuring the Mean Radiant Temperature is about 3 °C for Shaykh Zayed district and 1 °C for the Fifth Settlement district and this is due to the materials absorption and emissions for the long and short waves, respectively.